Analisis Kebutuhan Asesmen Kemampuan Pemecahan Masalah Matematika Berbasis Teslet untuk Siswa Sekolah Menengah Kejuruan - Laeli Muzamilah; Dewi Amaliah Nafiati; Suriswo Suriswo (Media Pendidikan Matematika, 2026)
Problem-solving ability is an essential 21st-century competency required by vocational high school (SMK) students to face the increasingly complex and dynamic demands of the workforce. However, the current assessment practices in SMKs remain conventional and are inadequate in capturing students’ thinking processes comprehensively. This study aims to analyze the needs for a problem-solving assessment in mathematics, which will serve as the foundation for developing a testlet-based assessment instrument that aligns with students' vocational expertise and workplace relevance. A descriptive research method with both qualitative and quantitative approaches was employed, involving 338 students, 4 school principals, and 16 mathematics teachers from private SMKs in Brebes Regency. Data were collected through interviews, questionnaires, and observations. The findings reveal that the majority of students, teachers, and school principals recognize the need for an innovative assessment model that evaluates not only the final answers but also the stages of students’ problem-solving processes. A testlet-based assessment guided by Polya’s problem-solving theory is considered relevant and applicable to the SMK context, as it enhances student engagement, critical thinking skills, and the real-world application of mathematics. Nonetheless, challenges persist, including limited time, teacher readiness, and the need for targeted training and implementation guidelines. This needs analysis provides a solid foundation for designing a valid, contextually relevant assessment instrument that can enhance the quality of mathematics learning in vocational schools.